In situ preparation of magnetic Fe₃O₄-chitosan nanoparticles for lipase immobilization by cross-linking and oxidation in aqueous solution - Wu, Yue; Wang, Yujun; Luo, Guangsheng; Dai, Youyuan (Bioresource technology, 2009)
A new and simple method has been proposed to prepare magnetic Fe₃O₄-chitosan (CS) nanoparticles by cross-linking with sodium tripolyphosphate (TPP), precipitation with NaOH and oxidation with O₂ in hydrochloric acid aqueous phase containing CS and Fe(OH)₂, and these magnetic CS nanoparticles were used to immobilize lipase. The effects on the sequence of adding NaOH and TPP, the reaction temperature, and the ratio of CS/Fe(OH)₂ were studied. TEM showed that the diameter of composite nanoparticles was about 80nm, and that the magnetic Fe₃O₄ nanoparticles with a diameter of 20nm were evenly dispersed in the CS materials. Magnetic measurement revealed that the saturated magnetisation of the Fe₃O₄-CS nanoparticles could reach 35.54emu/g. The adsorption capacity of lipase onto nanoparticles could reach 129mg/g; and the maximal enzyme activity was 20.02μmolmin⁻¹ mg⁻¹ (protein), and activity retention was as high as 55.6% at a certain loading amount.